A specific mapping between topological superconductors and topological insulators. (1st September 2017) - Lin, Yang; Hao, Weichang; Guo, Huaiming
Abstract: An interesting mapping between topological insulators (TI) and topological superconductors (TS) is presented. We show that if a Hamiltonian of a TI is purely imaginary, there is a corresponding TS with the Hamiltonian in the same form, but under a Majorana basis. Starting from the well-known TI in different dimensions, we perform the mapping explicitly. New TS systems and new understanding of the known TS are obtained. The result provides a natural way to construct topological nontrivial gapped Majorana systems, which may be engineered in the experimental setups with Majorana quasiparticles as the low-energy excitations.